The power-proportion method for intracranial volume correction in volumetric imaging analysis - Liu, Dawei; Johnson, Hans J.; Long, Jeffrey D.; Magnotta, Vincent A.; Paulsen, Jane S. (Frontiers in Neuroscience, 2014)
In volumetric brain imaging analysis, volumes of brain structures are typically assumed to be proportional or linearly related to intracranial volume (ICV). However, evidence abounds that many brain structures have power law relationships with ICV. To take this relationship into account in volumetric imaging analysis, we propose a power law based method—the power-proportion method—for ICV correction. The performance of the new method is demonstrated using data from the PREDICT-HD study.